Individual and Institutional Factors Influencing Student’s Decision to Choose an Education Institution within Kathmandu Valley - Bajracharya, Shirasha (Nepalese Journal of Business, 2025)
The study examines the individual and institutional factors influencing student’s decision to choose an education institution within Kathmandu Valley. Student’s preference is selected as the dependent variables. The selected independent variables are college fee, location of college, quality education, college reputation, peer influence and academic programs. The primary source of data is used to assess the opinions of respondents regarding college fee, location of college, quality education, college reputation, peer influence, academic programs and student’s preferences. The study is based on primary data of 162 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and impact of individual and institutional factors on student’s preference to choose an education institution. The study demonstrated a positive impact of college fee on student’s preferences to choose an education institution within Kathmandu Valley. It indicates that when students find college fee affordable and fair, they are more likely to increase their preference and report increase in the number of students. Similarly, the study revealed a positive impact of location of college on student’s preferences. It indicates that better and safe location of college boost student’s confidence, leading to increased number of students. Likewise, the study showed a positive impact of quality education on student’s preferences. It indicates that higher and better the quality education higher will be the student’s preferences. Further, the study observed a positive impact of college reputation on student’s preferences. It indicates that better college reputation influences student’s preferences leading to increase in number of students. In addition, the study found a negative impact of peer influence on student’s preferences. It indicates that bad level of peer influence decreases student’s preferences to choose a particular educational institution. Moreover, the study identified a positive impact of academic programs on student’s preferences. It indicates that better academic programs associated with student’s preferences lead to increase in student’s admissions. These findings underscore the significant role of college fee, location of college, quality education, college reputation, peer influence and academic programs in shaping student’s preferences to choose an education institution within Kathmandu Valley.